Formative assessment : making it happen in the classroom - Heritage, Margaret (Thousand Oaks, California : Sage, 2021)
'Offers specific examples of the formative assessment process in action in a range of subject areas Addresses the place of formative assessment within the broader assessment picture Discusses and gives examples of effective feedback as an essential part of formative assessment Shows how to engage students in self-assessment and self-management so they can participate in keeping their learning on course Examines how educators and school leaders can support classroom implementation of formative assessment'--
Includes index.
Keywords: Educational tests and measurements; Effective teaching